Moeder, waarom werken wij zo hard? - van de Ven, Jeanneke; Leye, Marijke; Schoefs, Nicole (Brussel: Vlaams Overleg Duurzame Ontwikkeling (VODO), 1995)
"Jeanneke van de Ven; Marijke Leye; Nicole Schoefs... et al."